2010
DOI: 10.1103/physrevb.81.085407
|View full text |Cite
|
Sign up to set email alerts
|

Theory of interfacial charge-transfer complex photophysics inπ-conjugated polymer-fullerene blends

Abstract: We present a theory of the electronic structure and photophysics of 1:1 blends of derivatives of polyparaphenylenevinylene and fullerenes. Within the same Coulomb-correlated Hamiltonian applied previously to interacting chains of single-component π-conjugated polymers, we find an exciplex state that occurs below the polymer's optical exciton. Weak absorption from the ground state occurs to the exciplex. We explain transient photoinduced absorptions in the blend, observed for both above-gap and below-gap photoe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 49 publications
(116 reference statements)
1
33
1
Order By: Relevance
“…Sheng et al 48 demonstrated that polarons in P3HT:PCBM are created through two different channels: a direct, ultrafast one-step process and a slower, two-step process involving the creation and the dissociation of CT states, while Aryanpour et al 49 applied a Coulomb-correlated Hamiltonian to find that fully separated charge-pairs are not a direct photoexcitation in polymer:fullerene heterojunctions. These two works would suggest that in some systems the rapid charge separation dynamics argued here are not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Sheng et al 48 demonstrated that polarons in P3HT:PCBM are created through two different channels: a direct, ultrafast one-step process and a slower, two-step process involving the creation and the dissociation of CT states, while Aryanpour et al 49 applied a Coulomb-correlated Hamiltonian to find that fully separated charge-pairs are not a direct photoexcitation in polymer:fullerene heterojunctions. These two works would suggest that in some systems the rapid charge separation dynamics argued here are not observed.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In order to further improve performance of BHJs, including SMBHJs, it is important to understand mechanisms of charge carrier photogeneration, transport, and recombination, as well as their contribution to the photocurrent, in both pristine organic semiconductor materials and their D/A composites. Many recent studies have addressed dynamics and propensity for dissociation of CT states, [9][10][11][12][13][14][15][16][17][18][19] effects of D/A LUMO and HOMO energy offsets, [20][21][22][23][24] and of D/A molecular packing at the D/A interfaces, 25 in polymer-based BHJs, whereas relatively few studies have explored similar issues in SMBHJs. [26][27][28][29][30] For SMBHJs, of particular interest are solution-processable photoconductive organic semiconductors with high charge carrier mobilities and solid-state packing favoring efficient charge separation at the D/A interfaces.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7] The energetic position of the CTE, often determined by absorption spectroscopy, 5 exhibits a strong correlation with the V oc , as the CTE is an excitation described by a hole localized on the HOMO ͑polymer͒ and an electron on the LUMO ͑fullerene͒ . 8,9 The influence of CTE on J sc is more difficult to estimate but as well important for the photovoltaic efficiency. In polymer/ polymer blends it has been observed how the intensity of CTE ͑exciplex͒ emission is influencing the photocurrent, 10,11 although nonradiative decay of exciplexes into triplet intrachain excitons has been shown to compete with free carrier generation, 11,12 thus influencing a direct correlation between exciplex intensity and J sc .…”
mentioning
confidence: 99%